Relationship between pregnancy rate and number of intrauterine insemination cycles during the study of comparative efficacy of letrozole and clomiphene citrate adjuvants to gonadotropin stimulation in controlled ovarian stimulation cycles combined with intrauterine insemination therapy - Sharma, Pankaj; Verma, Ashok; Katoch, Kritika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Infertility is commonly defined as the failure of conception after at least twelve months of unprotected intercourse. Factors contributing are both male and female in which unexplained etiology accounts for 51%, male factor 28%, endometriosis 17% and ovulatory disorders 4%. Methods: Prospective, randomized study was conducted at DRRPG medical college, Tanda, Kangra, Himachal Pradesh. In our study, patients were randomized into two groups of 30 each. Women in group A received clomiphene citrate 100mg/day and group B received letrozole 2.5 mg/day from day 3-7 of menstrual cycle. All the patients received human menopausal gonadotropin 75 U given every alternate day from day 5 until HCG administration. Ovulation was triggered with recombinant HCG (5000 IUIM) when the dominant follicles reached 18 mm in diameter. A single IUI was performed 36 hours later. A maximum of four cycles were given. Results: In our study, total number of induction cycles given in group A and B were 120 and 114 respectively. Out of these, 112 and 111 IUI cycles were done in group A and B respectively. A pregnancy rate of 1.66% and 7.87% per IUI cycle was observed in group A and B respectively.Thus it is concluded that the pregnancy rates were significantly higher in letrozole group (30%) in comparison to clomiphene citrate group (6.66%). Conclusions: Aromatase inhibitor letrozole appears to constitute a good alternative to clomiphene citrate in patients with unexplained infertility undergoing gonadotropin-stimulated COS cycles combined with IUI therapy.